Implementasi Kurikulum Responsif Gender Pada Universitas di Indonesia - Heriberta, Heriberta; Sriayudha, Yayuk; Sartika, Delita; Wachyuni, Sri; Hastuti, Dwi (Syntax Corporation, 2025)
The implementation of a gender-responsive curriculum encourages the improvement of the quality of management and teaching processes in each learning unit which leads to efforts to improve the quality of education. This research, which is a continuation of previous research, focuses on the development of academic manuscripts and gender-responsive curriculum models. Now we are trying to evaluate more deeply from the planning, implementation, and evaluation stages of the learning process by referring to the principles of the gender equality curriculum. This study also explores qualitatively the implementation of gender-responsive curriculum applied in the learning process in Indonesia. The research method used was a focus group discussion attended by 10 respondents through methods and observations and as such because the instrument was to obtain information. The structured interviews also consisted of officials in the field of student affairs and alumni, the women's empowerment service and the police. Based on the results of the research, the criteria for a gender-responsive curriculum with the principle of equality in lectures in several courses in several study programs were obtained. Revising several one-semester lecture plans in several courses in several gender-responsive study programs. and adjust the criteria of the gender-responsive curriculum with the principles of gender equality. The future plan is to implement several courses by implementing changes to the one-semester lecture plan to include gender-responsive materials at the university level.